Quality of antenatal and childbirth care in northern Ghana - Duysburgh, Els; Williams, A.; Williams, J.; Loukanova, Svetla; Temmerman, M. (BJOG, 2014)
The QUALMAT research project aims to improve maternal and newborn health by improving the quality of antenatal and childbirth care provided in primary healthcare facilities. Within the frame of this project, a comprehensive quality assessment took place in selected health centres in northern Ghana. The results of this assessment showed that overall quality of routine antenatal and childbirth care was satisfactory, although some critical gaps were identified. Counselling and health education practices need to be improved; laboratory investigations are often not performed; examination and monitoring of mother and newborn during childbirth are inadequate; partographs are often not used and poorly completed; and equipment to provide assisted vaginal deliveries was absent.